Isolation of cellulolytic bacteria from soil and identification by 16S rRNA gene sequencing - Mahjabeen, Faria (BRAC University, 2017)
This thesis report is submitted in partial fulfillment of the requirement for the degree of B.Sc in Microbiology, 2016.